Design and Implementation of Reduced Fuel Consumption in Cement Kiln with Efficient Cooling Technology Using PLC and HMI - Navaneetha Krishnan, R; Ramamoorthy, K (International Journal of Engineering and Technology, 2018)
Cement is the most important essential component to the building infrastructure development. Taking into consideration that the bond market will record an expanding rate of 15 - 20%, identified with the private structures improvement and to the start of extensive foundation extends the concrete creation is of extraordinary premium, both from the perspective of item's quality increment and crude material utilization. The main objective of this paper is to show how the process model can be inserted into advanced controllers to allow the successful control and optimization of the process, thereby upgrading the new technologies to the cement kiln, hot air from the Grate cooler is recycled to the Pre-heater, in order to reduce the fuel consumption in burner and high production rate of the cement can be achieved. The cement kiln consists of DRY and WET process. Initially, in pyro-processing the raw mix is fed into cement kiln and heated up to 1500℃ in the presence of limited supply of oxygen, the resultant clinker is now allowed to cooldown up to 100℃. Waste hot air from the Grate cooler is recycled to the Pre-heater, in order to reduce the fuel consumption in burner. Process mechanization is the place the modern territory offers the greatest and most fulfilling challenges as far as joining customary building abilities with mechanical development. The cement kiln is enhanced with the new technology using PLC (Programmable Logic Controller) and the output is monitored and controlled with the help of the HMI (Human Machine Interface). The whole system has been implemented and tested using Siemen’s PLC.